WHEN AI ENTERS THE ENGLISH CLASSROOM: A THREAT TO LEARNING OR A PATHWAY TO CRITICAL THINKING? - Andi Hamzah Fansury (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
The rapid integration of Artificial Intelligence (AI) into English language learning has generated ongoing debate regarding its potential risks and benefits, particularly in relation to students’ critical thinking skills. This study aimed to investigate Indonesian EFL students’ perceptions of AI in English language learning by examining three dimensions: AI as a threat, AI as an opportunity, and AI as a support for critical thinking. Employing a descriptive quantitative research design, data were collected through a questionnaire administered to 90 undergraduate students from three universities in Makassar, Indonesia: Universitas Bosowa, Universitas Negeri Makassar, and Universitas Muhammadiyah Makassar. The data were analyzed using descriptive statistical techniques, including frequencies and percentages. The findings indicate that while students acknowledge potential risks associated with AI use, such as overreliance, these concerns remain moderate. In contrast, the majority of students perceive AI as a valuable learning tool that enhances English language learning and supports the development of critical thinking skills. Overall, the results suggest that AI is predominantly viewed as an opportunity rather than a threat in Indonesian EFL contexts. The study highlights the importance of pedagogical guidance in integrating AI to ensure that it functions as a cognitive support tool that promotes reflective and critical engagement in English language learning.